Analisis Faktor-Faktor yang Mempengaruhi Sentra Produksi Komoditi Kopi di Kabupaten Humbang Hasundutan - Albina Ginting; Hotden Leonardo Nainggolan; Gerald Siahaan (Jurnal Agrisep, 2017)
This study aims to determine the factors that affect the coffee production center and government policy in the development of coffee production in Humbang Hasundutan Regency. Data analysis method in this research is multiple linear regression analysis and descriptive analysis. Based on the research results can be concluded; (1) the average coffee farming area in Humbang Hasundutan is 0.7 ha, with an average production of 558 kg/ ha and average income of Rp. 5,833,092.5/ year and R C ratio 2.769 so coffee farming in this area is efficient, (2) Value adjusted R2 is 0.832 can be interpreted 83.2% variable of coffee farming production explained variable; (3) Variable area of land and venture capital have positive and significant effect to coffee farming production in Humbang Hasundutan Regency, (4) Government policy in the field of land, capital, price of coffee, education, experience, fertilizer price, it is not enough to ensure the availability of fertilizer, especially subsidized fertilizer, 56% of respondents said that the training of farmers in the framework of human resource development is not sufficient and 55% of respondents said the extension policy to farmers has not supported the development of coffee farming. Based on the result of research suggested to; a) the government facilitates farmers to gain access to capital to develop coffee farming in Humbang Hasundutan Regency, b) the government improves training and extension for farmers and ensures the availability of fertilizers, especially subsidized fertilizers, c) the government undertakes the development of human resources and the development of breeding technology to obtain superior seeds in order to develop coffee farming in Humbang Hasundutan Regency.